Persepsi Mahasiswa Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Sumatera Utara terhadap Pancasila sebagai Ideologi Negara - Ritonga, Alwi Dahlan; Kusmanto, Heri (Politeia: Jurnal Ilmu Politik, 2018)
This study is the study of the perception of the Students against the State ideology Pancasila at the USU extension. Focus students perceptions of social about how discuss USU against Pancasila. The findings of this study, among others, there are three things that become indicators of students perception in seeing against Pancasila. First, the indicators of cognition to see the level of knowledge of students against Pancasila;Â  Second, indicators of students feelings of affection to see concerns the emotional aspects toward Pancasila; Third, the evaluative indicators to see objectively based on student assessment of cognition and affection they have associated the Pancasila. The method used is the method diskriptif-quantitative data collection techniques with the shape of the survey (questionnaire) and data analysis techniques using univarial analysis with a single table.